Among women across worlds : North Korea in the global Cold War - Kim, Suzy, 1972- (Cornell University Press, 2023)
"Excavates the transnational linkages between women of North Korea and the world from the late 1940s to 1975, the year designated by the UN as International Women's Year, and offers a different genealogy of the global women's movement that centers the 'East' and the Third World"--